Kualitas dan Daya Terima Kue Mangkok Padat Gizi sebagai Makanan Anak Balita - Azda, Yessilvia; Baidar, Baidar; Yuliana, Yuliana (Journal of Home Economics and Tourism, 2015)
This study aimed to analyze the quality (shape, color, aroma, texture, flavor) and determine acceptability cupcakes spinach added nutrient dense red, purple sweet potato and milk. Type of research is the development by using 6 expert panelists who are experts in Tata catering lecturer, nutritional science and food science to test the validity produc. The object of research is nutrient dense cupcake. The procedure in this study is to determine the standard recipe and then tested. Further development of nutrient dense cupcake recipe with the addition of red spinach, purple sweet potato and milk. Cupcakes were developed then tested its validity by a panel of experts to cupcakes nutrient dense declared invalid. Further test acceptance dense cupcake nutrition to children under five with indicators such as many are eaten, expression of interst in food,Â  the length of time spent 1 cupcake nutrilitionally dense fruit cake. Validity test results Kue mangkok developed nutrient dense declared invalid. As many 65% of children under five spend a portion of cupcake given nutrient dense, and 60% of children under five show the expression of interest or eager to consume nutrient-dense cupcake, 75% of children under five spend portions of nutrient dense cupcake granted for less than 10 minutes. Key word: Quality, capacity acceptance, kue mangkok nutrient dense, toddlers